1996
DOI: 10.1093/ageing/25.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density, Bone Markers and Bone Radiological Features in Mastocytosis

Abstract: We examined the association between severity of disease in mastocytosis and skeletal manifestation and bone markers in 16 patients varying in extent of mastocytosis as determined by the urine excretion of methylimidazoleacetic acid. Both osteoporosis and osteosclerosis were found. Bone density in the hip was significantly higher (p < 0.05) in both men and women with an enhanced histamine metabolite excretion. Patients with only moderately increased mast cell mass had low bone mineral density in the hip, osteop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 17 publications
2
50
0
Order By: Relevance
“…In view of the studies discussed above the results of our study would suggest a U-shaped relationship between the total mast cell burden and BMD in the lumbar spine and hip regions [15,18,19]. We found the lowest BMD levels in patients with mildly and moderately elevated mast cell mass, corresponding to BST levels between approximately 30 and 100 ng/ml.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In view of the studies discussed above the results of our study would suggest a U-shaped relationship between the total mast cell burden and BMD in the lumbar spine and hip regions [15,18,19]. We found the lowest BMD levels in patients with mildly and moderately elevated mast cell mass, corresponding to BST levels between approximately 30 and 100 ng/ml.…”
Section: Discussionsupporting
confidence: 57%
“…Table 4 and Z-score values (Z-Score) of the lumbar spine, total hip and femoral neck region. [19]. In contrast, BMD was higher in patients with more strongly elevated mast cell mass (methylimidazoleacetic acid values 7.5 and 8.6 times the upper limit of the reference range).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies demonstrated the abundance of histamine synthesizing and catabolizing enzymes in bone and bone marrow (26,27). Moreover, the bone abnormalities in patients with mastocytosis and high circulating levels of histamine are well documented (28). These patients often develop osteoporosis, because of increased bone resorption primarily at the ends of the long bones (20).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase cleavage of ICAD releases it from CAD, thereby activating CAD, which degrades DNA between nucleosomes. Third, caspases cleave several enzymes which sense or repair damaged DNA, including poly (ADP-ribose) polymerase (PARP), RAD21, RAD5 1, ATM, the catalytic subunit of the DNA-dependent protein kinase, the Bloom Syndrome protein (BLM), and BRCA1 (24)(25)(26)(27)(28)(29)(30)(31). In the case of RAD21, caspase cleavage generates a proapoptotic carboxyl terminal product that is sufficient to induce apoptosis (25,26).…”
Section: Bodymentioning
confidence: 99%
“…Intriguingly, experiments performed with cells derived from caspase-3 knockout mice or with caspase-3-deficient MCF-7 cells have revealed that caspase-3 is required for apoptotic chromatin condensation and DNA fragmentation, perhaps because ICAD proteolysis, and therefore CAD activation, is impaired in the absence of caspase-3 (16,55,56). MLH1, then, can be added to a short list of caspase-3-specific substrates, which also includes other proteins involved in DNA repair such as RAD51, BLM, and topoisomerase 1 (27,30,57). Human MLH1 is cleaved at a DXXD consensus caspase-3 cleavage motif (58, 59) (DKTD 418 ,I-419 ) near the mid region of the protein.…”
Section: (Etoposide) Mlhl Is Selectively Cleaved By Caspase-3 (But Nmentioning
confidence: 99%